The vicious circle: how systemic barriers perpetuate maternity interpreting service inadequacies for migrant women in the UK - Li, Li (Frontiers in Global Women's Health, 2025)
IntroductionMigrant women who speak languages other than English in the UK face elevated risks of adverse birth outcomes and experience significant maternal health disparities, conditions exacerbated by persistent inadequacies in interpreting service availability, quality, and costs. While video-mediated interpreting has been proposed as a solution, little is known about the systemic barriers that might limit its effectiveness in real-world settings.MethodsThis study employed a transformative mixed-methods approach to investigate systemic barriers in maternity interpreting services, focusing on interpreter retention, service availability, and video-mediated interpreting implementation, specifically LanguageLine Solutions' interpreter-on-wheels (IOW). Data were collected in the UK between 2019 and 2022 from seven key stakeholder groups: Migrant women (n = 24), support workers (n = 10), maternity care professionals (n = 46), interpreters (n = 159), bilingual health advocates (n = 7), language service providers (n = 6) and a commissioner. Semi-structured interviews, surveys, focus groups, ethnographic observations and service provider data were analysed using reflexive thematic analysis and descriptive statistics.ResultsThe analysis revealed three interconnected systemic barriers forming a vicious circle in interpreting service provision: (1) Constrained user agency, where migrant women prioritised basic access to any interpreting support over preferences for service quality due to systematic service failures; (2) interpreter workforce sustainability crisis, with nearly 60.4% of interpreters having decreased or stopped healthcare interpreting assignments due to poor remuneration and better opportunities elsewhere; (3) infrastructure implementation failures, with interpreter-on-wheels implementation hampered by unreliable infrastructure, achieving only 11% utilisation despite its potential benefits.DiscussionThese findings demonstrate how interpreting service challenges form an interconnected system where workforce issues, technical infrastructure, and institutional practices mutually reinforce one another, creating a vicious circle that perpetuates service inadequacies. This study advances understanding of the systemic nature of interpreting service challenges in maternity care for migrant women and highlights the need for coordinated interventions that address multiple interconnected barriers simultaneously, rather than isolated technological solutions.